Atmospheric Abundances, Trends and Emissions of CFC-216ba, CFC-216ca and HCFC-225ca - Corinna Kloss; Mike J. Newland; David E. Oram; Paul J. Fraser; Carl A. M. Brenninkmeijer; Thomas Röckmann; Johannes C. Laube (Atmosphere, 2014)
The first observations of the feedstocks, CFC-216ba (1,2-dichlorohexafluoropropane) and CFC-216ca (1,3-dichlorohexafluoropropane), as well as the CFC substitute HCFC-225ca (3,3-dichloro-1,1,1,2,2-pentafluoropropane), are reported in air samples collected between 1978 and 2012 at Cape Grim, Tasmania. Present day (2012) mixing ratios are 37.8 ± 0.08 ppq (parts per quadrillion; 1015) and 20.2 ± 0.3 ppq for CFC-216ba and CFC-216ca, respectively. The abundance of CFC-216ba has been approximately constant for the past 20 years, whilst that of CFC-216ca is increasing, at a current rate of 0.2 ppq/year. Upper tropospheric air samples collected in 2013 suggest a further continuation of this trend. Inferred annual emissions peaked 421 at 0.18 Gg/year (CFC-216ba) and 0.05 Gg/year (CFC-216ca) in the mid-1980s and then decreased sharply as expected from the Montreal Protocol phase-out schedule for CFCs. The atmospheric trend of CFC-216ca and CFC-216ba translates into continuing emissions of around 0.01 Gg/year in 2011, indicating that significant banks still exist or that they are still being used. HCFC-225ca was not detected in air samples collected before 1992. The highest mixing ratio of 52 ± 1 ppq was observed in 2001. Increasing annual emissions were found in the 1990s (i.e., when HCFC-225ca was being introduced as a replacement for CFCs). Emissions peaked around 1999 at about 1.51 Gg/year. In accordance with the Montreal Protocol, restrictions on HCFC consumption and the short lifetime of HCFC-225ca, mixing ratios declined after 2001 to 23.3 ± 0.7 ppq by 2012.